EFFECT OF POMEGRANATE (Punica granatum) JUICE ON PLASMA NITRIC OXIDE LEVELS AND ANTIOXIDANT STATUS IN ISOLATION STRESS AND HEAT STRESS INDUCED RATS - V. Beckseeba Lavanya; A. Thangavel; V. Leela; S. Selvasubramanian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was undertaken to assess the effect of pomegranate (Punica granatum) juice (PJ) supplementation on plasma nitric oxide (NO) levels and antioxidant status in isolation stress induced and heat stress induced rats. Thirty adult male Wistar albino rats of 140-150 g body weight were randomly divided into five groups of six each viz., control, isolated stress induced, isolation stress induced supplemented with PJ, heat stress induced and heat stress induced supplemented with PJ. Blood samples were collected at weekly interval during four weeks of the experimental period, plasma samples were separated and stored at -200C for the assay of nitric oxide (NO) levels, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) activities and lipid peroxidation levels. PJ supplementation to isolated stress induced and heat stress induced rats significantly (Pd” 0.05) increased plasma nitric oxide (NO) levels, SOD, CAT and GSH-Px activities, whereas plasma lipid peroxidation level was significantly lowered (Pd” 0.05) in comparison with respective stress induced models and control groups.